Thermo-alkaline treatment. A process that changes the thermal properties of corn starch - Pineda-Gómez, Posidia; Coral, Diego F; Ramos-Rivera, David; Rosales-Rivera, Andres; Rodríguez-García, Mario E (Procedia food science, 2011)
This research focuses on the study of the thermal properties of starch corn processed using thermo-alkaline treatment. Using Modulated Differential Scanning Calorimetry (MDSC) these investigators studied the changes during gelatinization of starch in alkaline solution water-calcium hydroxide Ca(OH)2 at concentrations from 0.1 to 0.3% (g Ca(OH)2 /g dry starch). The scanning was carried out at 80% (w/w) moisture and 5°C/min in nitrogen environment. Similarly, thermogravimetric analysis (TGA) was used to study the thermal degradation of starch treated utilizing this method. The treated starch was subjected to heating ramps from Troom to 800°C using different rates. The MDSC results indicate that the interaction of calcium ions and starch shifts the gelatinization peak to higher temperatures when the concentration increases. In the same manner results show changes in the enthalpy values of the transition compared to when gelatinization occurs only in the presence of water. However, the disruption power of alkali has a limit. On the other hand, TG data of the principal stage of degradation permitted to find the activation energy of raw and treated corn starch, using Friedman, Flynn-Wall-Ozawa and also Kissinger methods. TGA analysis demonstrated that thermo-alkaline treatment with Ca(OH)2, had a decelerator role in thermal degradation of corn starch. More complete knowledge of activation energy as a barrier to initiate decomposition process helped in the understanding of thermal decomposition stability of corn starch when thermo-alkaline treatment is used in food industry.